2018
DOI: 10.1017/pen.2018.15
|View full text |Cite
|
Sign up to set email alerts
|

A Computational Network Control Theory Analysis of Depression Symptoms

Abstract: Rumination and impaired inhibition are considered core characteristics of depression. However, the neurocognitive mechanisms that contribute to these atypical cognitive processes remain unclear. To address this question, we apply a computational network control theory (NCT) approach to structural brain imaging data acquired via diffusion tensor imaging in a large sample of participants, to examine how NCT relates to individual differences in subclinical depression. Recent application of this theory at the neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 98 publications
0
8
1
Order By: Relevance
“…Neuropsychiatric disorders are considered to be dysconnectivity syndromes, and graph theory has previously been used to quantify the variations in functional and structural network properties, which can be used to explore various disorders (Bullmore and Sporns, 2009;Nakamura et al, 2009;Kim et al, 2019). A previous DTI study found that depression is correlated with complex brain networks by network controllability analysis, yet the chosen partitions of brain modularity might bias its result (Kenett et al, 2018). Hence, we adopted graph theoretical analysis to investigate network alternations.…”
Section: Introductionmentioning
confidence: 99%
“…Neuropsychiatric disorders are considered to be dysconnectivity syndromes, and graph theory has previously been used to quantify the variations in functional and structural network properties, which can be used to explore various disorders (Bullmore and Sporns, 2009;Nakamura et al, 2009;Kim et al, 2019). A previous DTI study found that depression is correlated with complex brain networks by network controllability analysis, yet the chosen partitions of brain modularity might bias its result (Kenett et al, 2018). Hence, we adopted graph theoretical analysis to investigate network alternations.…”
Section: Introductionmentioning
confidence: 99%
“…This approach has the potential to inform theories of dynamic cognitive processes, clinical neuroscience, neurodegeneration, and brain reserve. Specifically, there is evidence that these global brain state transitions are impaired in clinical populations (Braun et al, 2019 ; Jeganathan et al, 2018 ; Kenett, Beaty, & Medaglia, 2018 ) and that such impairments can be traced back to specific driver nodes (Jeganathan et al, 2018 ; Kenett, Beaty, et al, 2018 ; Muldoon et al, 2016 ; Zoeller et al, 2019 ). However, thus far, these control properties have been exclusively derived from WM fiber tracts without the consideration of gray matter (GM) properties.…”
Section: Introductionmentioning
confidence: 99%
“…In a broad sense, cognitive control in the language domain is a special case of a network control problem for the brain (Medaglia, 2019): how does the brain achieve the neural states necessary to produce context-appropriate responses? Since the first theoretical network controllability analyses in large scale diffusion MRI networks (Gu et al, 2015), NCT has been used to characterize the energy required to integrate or segregate network activity (Betzel et al, 2016;Gu et al, 2017;Tang et al, 2017;Wu-Yan et al, 2018), identify correlates of cognitive function in and out of the executive domain (Kenett et al, 2018a(Kenett et al, , 2018bCornblath et al, 2019;Lee et al, 2019), and predict or correlate the effects of brain stimulation on the brain and behavior (Khambhati et al, 2019;Medaglia et al, 2018a;Beynel et al, 2019;Stiso et al, 2019).…”
Section: Introductionmentioning
confidence: 99%